Radicalisation: Conceptual and Explanatory Approaches - Kreshan, Basheer (Jordan Journal of Social Sciences, 2021)
This paper aims to identify Radicalism in a conceptual approaches and explanatory factors of this phenomenon, which still occupies human thought in societies. It returns to exaggeration, extremism, unilateralism in thinking, opinion, and abolition of the mind, And sometimes the main reason for it is the spread of ignorance and backwardness. It is linked to the religious, cultural, political, social and economic conditions of societies, but has taken on new dimensions in modern societies, especially when this type of extremism has been associated with violence and terrorism ,it has become a very serious and complex problem, and one of the most controversial topics in the modern world, especially after the events of September 11, 2011, and therefore, it is not easy to differentiate terrorism from extremism. Extremism takes a pattern of association, closure, and intolerance of opinion, refusing to accept the other's point of view, wether they are individuals or a group, does not believe in diversity of opinions, ideas and views, he rejects dialogue and coexistence with others and their ideas. It may go beyond the religious and political atonement of others, and the risk of extremism increases when it moves from the stage of wrong thought, belief and theoretical conception, to the embodiment through extremist practices and behaviors, which are expressed in violence, using all means to Achieving goals.